Effect of Aging Parameters of EN AW-7021 Aluminium Alloys on Stress Corrosion Cracking - S. Boczkal; M. Węgrzyn; W. Szymański; J. Bem; K. Wala; B. Płonka; D. Leśniak; M. Nowak (Archives of Metallurgy and Materials)
The main assumption of the conducted research was the selection of appropriate heat treatment parameters to obtain the best possible resistance to stress corrosion cracking (SCC) and the highest strength properties of the extruded profiles. The work selected the temperature and time of one- and two-stage treatment of the EN AW-7021 alloy based on aging curves. Tests carried out for samples after aging at 135°C for 24 h and two-stage aging at 90°C/8 h + 135°C/8 h revealed the highest resistance to SCC. The 7021 alloy, after heat treatment at 90°C/8 h + 135°C/16 h, reached the highest tensile strength of 534MPa. Transmission electron microscopy (TEM) observations showed slight differences in the finely dispersed nucleoids between the selected parameters of the artificial aging process.